2020
DOI: 10.1002/dys.1652
|View full text |Cite
|
Sign up to set email alerts
|

Early and late diagnosed dyslexia in secondary school: Performance on literacy skills and cognitive correlates

Abstract: Although a diagnosis of dyslexia is often made during elementary school, severe and persistent literacy difficulties of a considerable group of students are only noticed during secondary school. The question arises whether the literacy(‐related) deficits of these late identified students with dyslexia differ from those of early diagnosed students. To address this question, 10th Grade Dutch secondary school students with early ( n = 35) and late ( n = 19) identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 53 publications
(86 reference statements)
3
31
0
1
Order By: Relevance
“…Even though they used many different measures, Ransby and Swanson (2003) did not study the role of spelling skills when explaining TRF scores, although research on children and adolescent with dyslexia has shown a reciprocal relationship between decoding and visual word recognition skills, on the one hand, and spelling skills on the other ( Berninger et al, 2008 ; Bazen et al, 2020 ). Furthermore, the involvement of spelling skills in the reading of adults with dyslexia has been little studied, probably because research on this point has shown a persistent deficit in these skills.…”
Section: Introductionmentioning
confidence: 99%
“…Even though they used many different measures, Ransby and Swanson (2003) did not study the role of spelling skills when explaining TRF scores, although research on children and adolescent with dyslexia has shown a reciprocal relationship between decoding and visual word recognition skills, on the one hand, and spelling skills on the other ( Berninger et al, 2008 ; Bazen et al, 2020 ). Furthermore, the involvement of spelling skills in the reading of adults with dyslexia has been little studied, probably because research on this point has shown a persistent deficit in these skills.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to Gagliano et al we might expect the difference between oral and silent reading to be smaller in adolescents with dyslexia compared to typically developing peers, indicating a relatively strong impairment in silent as compared to oral reading. In contrast, based on findings of van den Boer et al ( 2014 ) on the stronger involvement of rapid naming in oral compared to silent reading, we might expect stronger deficits in oral as compared to silent reading, as rapid naming tends to be impaired in adolescents with dyslexia (e.g., Bazen et al, 2020 ; Torppa et al, 2015 ).…”
Section: Introductionmentioning
confidence: 79%
“…Although this measurement of reading fluency corresponds to the definition of dyslexia, it is at odds with daily experiences that more often require silent reading fluency, and reading of texts rather than words. This issue is especially relevant since dyslexia is a lifelong condition, and even though dyslexia is often diagnosed in elementary school, there are students who receive a diagnosis of dyslexia only later on in their school career, around Grade 7/8 or even later (e.g., Bazen et al, 2020 ; Torppa et al, 2015 ). At this (st)age, silent reading, text reading fluency, and comprehension of text are central to the school curriculum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using Dutch 10th-graders (mean age: 16.5 years) who had an early or late diagnosis of dyslexia and PA, RAN, and VAS tasks, Bazen et al [ 25 ] also examined the extent to which dyslexics had particular disorders. They found 31% of their sample had a VAS weakness and 63% and 60% had RAN and PA weaknesses, respectively.…”
Section: Results From the Studiesmentioning
confidence: 99%